(untitled) (Transport systems and technologies, 2018)
The problems of reforming the railway transport of Ukraine. The urgency of updating rolling stock. It was noted that one of the priorities of railway development is the achievement of high technical and economic performance of the transportation process in the railway sector. The above achievement is due to the decision of tasks required to ensure the performance and reliability of modern systems of traction and multiple units, which determine the safety of trains. Stressed that the main role among such systems drainage system air supply. The features of modern systems of air supply traction and railcar rolling stock, as well as provide their corresponding block diagrams. It noted the expediency of work towards the improvement of these systems in order to improve technical and economic performance of the rolling stock and the transportation process on the railways of Ukraine as a whole.